The first ever spectrum auction in Poland: Assumptions, expectations, results - Jerzy Kubasik (International Telecommunications Society (ITS), 2014)
So far no general exclusive frequency licenses have been granted in Poland through an auction. In the Regulatory Strategy until 2015, President of the Office of Electronic Commu-nications pointed to auction as a method of choosing companies which will be granted fre-quency licenses from 800 MHz band (so called digital dividend). The auction has been sched-uled to take place at the turn of 2013 and 2014, and is considered the biggest event of 2014 on the Polish telecommunications market. The article presents the main assumptions of the first ever spectrum auction in Poland on the basis of materials for auction assumptions' consulta-tions, auction documentation, opinions of entities involved that have been submitted during consultations as well as the position of the President of UKE. The author focuses on threats to execution of the auction itself as well as implementation of its results. The text is preceded by a short description of the Polish telecommunications market, especially in terms frequencies owned by the main players on this market, including their joint ventures and capital connec-tions.
Keywords: 330; regulation; spectrum auction; mobile services; LTE